A Garden of One's Own : A Collection of Modern Chinese Essays, 1919-1949 - Tam, King-fai; Tam, King-fai (Book collections on Project MUSE., 2013)
Fifty essays by thirty Chinese writers bring to vivid life a period in which modernization and republicanism coexisted within classical Chinese culture. Unlike the more thematically social and political fiction of the May Fourth movement, these xiaopin wen, or modern essays, address their readers with a unique intimacy, adopting a highly "personal" voice that is quietly meditative, lyrical, discreet, and full of wit and melancholy. Tam King-fai supplies critical literary and historical background on the relationship between xiaopin wen and the May Fourth movement, and with and commentary he explicates the form's lyric aestheticism.